Nephrotic syndrome induced Hypothyroidism - A case report - Alam, ABMM; Hasan, ANMS; Khan, AH; Banik, SK; Begum, SA; Hossain, D; Quader, MMU; Begum, R (Northern International Medical College Journal, 2013)
DOI: http://dx.doi.org/10.3329/nimcj.v4i2.15839 Northern International Medical College Journal Vol.4(2) 2013: 280-282